The Role of Mangrove Conservation in Sustainable Tourism - Dhyani Danaparamita, Edwina; ., Nadiroh; Safitri, Desy (KnE Social Sciences, 2020)
The rapid growth of the tourism industry in Indonesia has encouraged innovation in the sector as each business competes to attract domestic and foreign tourists. At the same time, however, this growth is having a negative impact of environmental damage such as water pollution and soil pollution, and also producing a perceived community loss. One option is to reduce the negative impact of tourism is by encouraging the development of ecotourism activities. For example, nearby communities could be encouraged to participate in the management of mangrove conservation ecotourism areas. This study considers how such communities can work with local governments on these projects. This complements traditional beliefs within the Indonesian culture which held that ancestors entrust natural wealth to their descendants to be guarded and utilized wisely. Keywords: conservation, mangrove, sustainable tourism